Two new species of dragon millipedes, genus Desmoxytes Chamnerlin, 1923, from Laos (Diplopoda: Polydesmida: Paradoxosomatidae), with redescriptions of all four species of Attems from Vietnam - Likhitrakarn, Natdanai; Golovatch, Sergei I.; Panha, Somsak (Zootaxa, 2015)
Two new species of Desmoxytes are described and abundantly illustrated: D. rhinoceros sp. n. and D. rhinoparva sp. n., from southern and northern Laos, respectively. Illustrated redescriptions of all four Vietnamese Desmoxytes species proposed by Carl Attems are also provided, based on type material.